Increase of radar-tracking seeming centre coordinates measurement accuracy in anti-aircraft GUN-missile complex - E. N. Builou; S. A. Gorshkov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The analysis of features of influence range and angular noise of the purpose on accuracy of measurement of co-ordinates in antiaircraft pushechno-rocket complexes is carried out. The way of increase of accuracy of measurement of co-ordinates of the seeming centre of radar-tracking object in a broadband monopulse radar of support is considered.